THE PRESTIGE OF MUSIC SCHOOLS IN THE FERGHANA PROVINCE WITHIN THE REPUBLIC AND THE INTERNATIONAL ARENA DURING THE INDEPENDENCE YEARS - Akbarova Nigora A’zamxonovna (Western European Studies, 2024)
This article illuminates data concerning the involvement and analysis results of music schools in the Fergana province before and during the periods of independence years, as well as their participation in international and republic competitions. Throughout the research both the achievements and obstacles encountered in the performances of music and art schools are elucidated, meanwhile the primary objective of the study is to illustrate the societal significance of these educational establishments by scrutinizing their engagement in international and republic competitions. The information delineated in this article underscores its historical, singular, analytical, and comparative-logical pertinence. Furthermore, it undertakes the task of exploring and utilizing information pertaining to this subject matter from contemporary archives of music schools, regional archive funds, and press publications. Amatuer researchers who will be engaged in the study within the realms of musical culture and the history of music education may derive value from the information expounded in this article. Moreover, this article offers insights into republic and international competitions conducted within the domain of music and art.
Keywords: republic; international; concerning